Pengaruh Personality Traits dan Individual Performance Terhadap Perilaku Intrapreneurial Karyawan pada Shopee Xpress Yogyakarta Hub - Deliani Azmi Zakiah Ahmad; Ratih Purbasari; Margo Purnomo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Intrapreneurial behaviour is an approach at the individual level that is carried out in a bottom-top manner by employees. Personality traits and individual performance are important to note in an organization to see whether these two things can encourage employees to have intrapreneurial behavior that can benefit the organization. This study used data collection methods through questionnaires using a sample of 67 respondents. The data that has been collected is then processed using the Statistical Package for Social Science (SPSS). The results of this study show that personality traits have a positive effect on intrapreneurial behavior and individual performance has a positive effect on intrapreneurial behavior. Furthermore, personality traits and individual performance simultaneously have a positive effect on intrapreneurial behaviour.